Potential Land Suitability for Cardamom (Elettaria cardamomum) Cultivation in Topos District, Lebong Regency - Kuswara, Dio Afrizal; Hindarto, Kanang Setyo; Utami, Kartika; Barchia, Muhammad Faiz; Widiyono, Heru (TERRA : Journal of Land Restoration, 2024)
Land suitability evaluation is crucial for determining the characteristics and quality of land to support cardamom cultivation. This study aims to map land suitability classes and assess the potential for cardamom cultivation in Topos District, Lebong Regency. Conducted from June to December 2023, the research employed survey methods, land classification, and descriptive presentation of results. Tools such as Avenza Map, soil augers, GPS, clinometers, Munsell Soil Color Charts, and laboratory soil analysis were used, supplemented with secondary data sources. Land suitability was determined using a matching technique for individual land characteristics. The results indicated that the actual land suitability for cardamom in Topos District is predominantly in the S3 class, covering 11,722.95 hectares (71.43%), limited by factors such as nutrient availability and steep slopes. Potential land suitability was classified into four categories: S1 (1,825.94 hectares, 11.12%), S1rc (727.35 hectares, 4.43%), S2rc (2,342.88 hectares, 14.27%), and S2 (5,326.63 hectares, 32.46%). Recommended improvements include liming, fertilization, organic matter application, and soil and water conservation to enhance land suitability. The most suitable areas for cardamom cultivation include shrubland, rice fields, open land, and mixed dryland farming. Economic analysis revealed a favorable B/C ratio of 1.11, signifying profitability. This study highlights the considerable potential for cardamom cultivation in Topos District, provided that sustainable land management practices are implemented. The findings underscore the crop’s economic viability, offering valuable insights for policymakers and farmers seeking to optimize land use while fostering economic growth and reducing environmental impact.